Evaluation of Rutting in Conventional and Rubberized Asphalt Mixes Using Numerical Modeling Under Repeated Loads - Saad, D. A.; Al-Baghdadi, H. A. (Engineering, Technology & Applied Science Research, 2021)
This research aimed to predict the permanent deformation (rutting) in conventional and rubberized asphalt mixes under repeated load conditions using the Finite Element Method (FEM). A three-dimensional (3D) model was developed to simulate the Wheel Track Testing (WTT) loading. The study was conducted using the Abaqus/Standard finite element software. The pavement slab was simulated using a nonlinear creep (time-hardening) model at 40°C. The responses of the viscoplastic model under the influence of the trapezoidal amplitude of moving wheel loadings were determined for different speeds and numbers of cycles. The results indicated that a wheel speed increase from 0.5Km/h to 1.0Km/h decreased the rut depth by about 22% and 24% in conventional and rubberized asphalt mixes, respectively. Moreover, increasing the number of cycles from 7,500 (15,000 passes) to 15,000 (30,000 passes) under constant speed increased the rut depth by about 25% and 30% in conventional and rubberized asphalt mixes, respectively. Furthermore, the addition of Crumb Rubber (CR) to the asphalt reduced its rut depth by 55% compared to conventional asphalt.